Design and analysis of hydraulic in a heavy commercial vehicle by recovering energy during braking - Parman, S. (Asian Research Publishing Network, 2016)
This paper studied a hydraulic regenerative braking in heavy commercial vehicles. The study determined amount of energy that can be recovered during braking period first. The recovered energy came from kinetic energy exerted by the engine when the vehicle is slowing down. Then, the kinetic energy was partially transformed into hydraulic energy to be stored and be used for future acceleration. Only the energy efficiency of the hydraulic regenerative braking system was analysed. The main attention of the paper was focusing on the calculation of thermal energy that can be converted into hydraulic energy in order to be re-used for future acceleration. Â©2006-2016 Asian Research Publishing Network (ARPN).